2020
DOI: 10.2147/ott.s229432
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Clinical Significance of <em>PPEF1</em> as a Promising Biomarker and Its Potential Mechanism in Breast Cancer</p>

Abstract: Background: Breast cancer (BC) is the leading cause of malignancy death in females worldwide. While intense efforts have been made to elucidate the pathogeny, the molecular mechanism of BC remains elusive. Thus, this study aimed to investigate the role of PPEF1 in the progression of BC and further explore the better clinical significance. Methods: The diagnostic and prognostic values of elevated PPEF1 expression in BC were unveiled via public databases analysis. In addition, Gene Ontology (GO), Gene Set Enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Finally, while the molecular function of phosphatase encoded by PPEF1 is not known in detail, it has been connected to apoptosis regulation and the response to calcium (Ca 2+ is also second messenger controlling cell death) 64 . It exerts a tumorigenic role in breast cancer 65 and was found to be overexpressed in pancreatic carcinoma 66 which confirms both its prognostic value in LUAD (poorer survival when highly expressed) and literature data regarding lung cancer 64 .…”
Section: Discussionsupporting
confidence: 76%
“…Finally, while the molecular function of phosphatase encoded by PPEF1 is not known in detail, it has been connected to apoptosis regulation and the response to calcium (Ca 2+ is also second messenger controlling cell death) 64 . It exerts a tumorigenic role in breast cancer 65 and was found to be overexpressed in pancreatic carcinoma 66 which confirms both its prognostic value in LUAD (poorer survival when highly expressed) and literature data regarding lung cancer 64 .…”
Section: Discussionsupporting
confidence: 76%
“…In addition, COL10A1 is a carcinogenic marker involving the epithelial-to-mesenchymal transition in GC, which is regulated by the transforming growth factor beta1 (TGF-β1)-SRY-box transcription factor 9 (SOX9) axis ( 49 ). Along with being an unfavorable prognostic marker, PPEF1 is negatively associated with OS and metastasis-free survival of breast cancer ( 50 ). Lin et al.…”
Section: Discussionmentioning
confidence: 99%
“…The 50 genes (listed in the Supplementary Table 8) discovered by the proposed model include 16 genes, IQGAP3 (Hu et al, 2019), KIF4A (Xue et al, 2018), TSHZ2 (Yamamoto et al, 2011), MKI67 (Schmidt et al, 2007), TNXB (Hu et al, 2009), KIFC1 (Ogden et al, 2017), KDM5B (Catchpole et al, 2011), PPEF1 (Ye et al, 2020), RYR3 (Shrestha et al, 2012), TMEM132C , FANCD2 (Barroso et al, 2006), ATAD2 (Kalashnikova et al, 2010), KIF26B (Wang et al, 2013), BRCA2 (Wooster et al, 1995), BLM (Arora et al, 2015), and ARFGEF (Kim et al, 2011), which are reported to be directly associated with breast cancer by previous researches. Although the other 14 genes have not been verified by biological experiments, we further analyze the Gene Ontology and pathway enrichment to explore their impact on the tumor formation and progression.…”
Section: Biomarkers and Go/pathway Analysismentioning
confidence: 99%